Dibujando vivencias a través de la danza (2022)
This work is presented with the results of the research project "Drawing experiences through dance" that aims to collect the experiences and knowledge of the teacher Junior Augusto Murillo Madrigal, to visualize the artistic processes that have intervened in the creation of his staging and the international scope of the Ara Macao Dance Company between the years 2007 – 2021 in Villavicencio. The methodological technique of life history is assumed as a source of data for this research. Conceptual approach interviews and documentation review are used. The nonprobabilistic sampling technique is used through three teachers who incur in the artisticformative processes and five members of the Ara Macao dance company, where the trajectory of Junior Augusto Murillo Madrigal will be reflected in the form of three chapters where his personal and artistic exploration and work as a manager is narrated.